PELATIHAN PENERAPAN TEKNOLOGI FIBER GLASS PADA PERAHU TRADISIONAL DI DESA KARANGSONG - Erawan, Nur Purna; Halala, Habib Rizqon; Munir, Muhammad Ikhfan; Riyani, Widiya Desih Sapta (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Potential of marine fisheries in our country is very big, one of them in Indramayu. However, the people who tend to still use the traditional way of making or repairing boats resulted in utilization is not optimal. Karangsong fundamental problem is the inability of traditional fishing boats as a means of providing the arrest. An alternative form of boat made of fiberglass are very worthy to be a technological solution. Fiberglass technology has long been known, but its use by fishermen in the village of Indramayu especially Karangsong not optimal. Therefore, the need for training on the application of fiberglass technology. The program is expected to make the fishing communities get added value and simplify the process of making a boat that is necessary to improve the productivity of the fishermen. The method is performed in the implementation of this program for surveying, socialization programs to the community in the village Karangsong, preparation tools and place, giving General knowledge of fiberglass materials, training design boat design, the development of the use of resin, boat making, evaluation and monitoring. Result of this activity is increased knowledge about fiberglass fishing communities around and start applying fiberglass technology for repair and manufacture of traditional boats.